General attitudes toward and awareness of vaccines among students at a university in Northern Cyprus - (:unkn) unknown (My University, 2021)
Misinformation and movements against vaccines put public health at risk. This study investigated vaccine awareness and opinions on the anti-vaccination movement among students at three faculties of Eastern Mediterranean University. Data were collected by questionnaire. Exposure to anti-vaccination propaganda increased proportionally with the size of the cities where participants were born. In total, 88.6% of the participants declared that they planned to vaccinate their children, while those who did not cited various reasons including the belief that vaccines do not work, that vaccines are harmful, and that it is better to be infected naturally. 60.6% of participants reported that they would get vaccinated against SARS-CoV-2 if there was an effective vaccine. Meanwhile, 24.5% of participants were not sure whether would get vaccinated even if it were possible, 11.4% of participants stated that they would not vaccinate their children for a variety of reasons. These results are important, especially in the context of a pandemic, because students will become leaders in education, business, and media, and thus shape the thoughts and opinions of future generations. The anti-vaccination movement is building momentum, and is especially influential in big cities; therefore, it is vital to change our approach to informing students about vaccination.
Keywords: Humans; Cross-Sectional Studies; Health Knowledge, Attitudes, Practice; COVID-19; SARS-CoV-2; Students; Vaccination; pandemic; Universities; Vaccines; anti-vaccination movement; college students; Cyprus; Vaccine